Investigations of effect of phase change mass transfer rate on cavitation process with homogeneous relaxation model. (December 2017) - He, Zhixia; Zhang, Liang; Saha, Kaushik; Som, Sibendu; Duan, Lian; Wang, Qian
Abstracts: The super high fuel injection pressure and micro size of nozzle orifice has been an important development trend for the fuel injection system. Accordingly, cavitation transient process, fuel compressibility, amount of non-condensable gas in the fuel and cavitation erosion have attracted more attention. Based on the fact of cavitation in itself is a kind of thermodynamic phase change process, this paper takes the perspective of the cavitation phase change mass transfer process to analyze above mentioned phenomenon. The two-phase cavitating turbulent flow simulations with VOF approach coupled with HRM cavitation model and U-RANS of standard k-ε turbulence model were performed for investigations of cavitation phase change mass transfer process. It is concluded the mass transfer time scale coefficient in the Homogenous Relaxation Model (HRM) representing mass transfer rate should tend to be as small as possible in a condition that ensured the solver stable. At very fast mass transfer rate, the phase change occurs at very thin interface between liquid and vapor phase and condensation occurs more focused and then will contribute predictably to a more serious cavitation erosion. Both the initial non-condensable gas in fuel and the fuel compressibility can accelerate the cavitation mass transfer process.